The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1021/acsami.6b16629
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Orthorhombic Perovskite-Type ZnSnO3 Single-Crystal Nanoplates and Their Application in Energy Harvesting

Abstract: In recent years, lead-free piezoelectric nanogenerators have attracted much attention because of their great potential for harvesting energy from the environment. Here, we report the first synthesis of two-dimensional (2D) single-crystal ZnSnO hexagon nanoplates and the fabrication of ZnSnO nanoplate-based nanogenerators. The orthorhombic perovskite-structured ZnSnO nanoplates with (111) facets of the exposed plate surface are successfully synthesized via a one-step hydrothermal reaction. Piezoelectric nanogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(55 citation statements)
references
References 48 publications
(82 reference statements)
1
54
0
Order By: Relevance
“…In order to improve the output performance of PENG, finding new materials with higher piezoelectric coefficients has become the most directed method. Up to now, various types of PENGs have been reported, such as PbZrTiO 3 (PZT), BaTiO 3 (BTO), (1− x )(PbMg 1/3 Nb 2/3 O 3 )– x (PbTiO 3 ) (PMN–PT), GaN, and ZnSnO 3 . Among them, PZT and PMN–PT, with high piezoelectric properties, have been investigated and applied extensively as piezoelectric materials candidates.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the output performance of PENG, finding new materials with higher piezoelectric coefficients has become the most directed method. Up to now, various types of PENGs have been reported, such as PbZrTiO 3 (PZT), BaTiO 3 (BTO), (1− x )(PbMg 1/3 Nb 2/3 O 3 )– x (PbTiO 3 ) (PMN–PT), GaN, and ZnSnO 3 . Among them, PZT and PMN–PT, with high piezoelectric properties, have been investigated and applied extensively as piezoelectric materials candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Since last decade, ternary transition metal oxides (TTMOs) have gained tremendous popularity in the field of photocatalysis by the scientific community. To exploit solar light more efficiently, photocatalysts with narrow band gap (e.g., ZnSnO 3 [ 2 ], Bi 2 WO 6 [ 3 ], Ce(MoO 4 ) 2 [ 4 ] and ZnFe 2 O 4 [ 5 ]) have been used, for absorbance of solar light in the visible region. Among ternary metal oxides, transition metal ferrites have drawn a great attention in the field of photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…ZnSnO 3 , including a polar LiNbO 3 (LN)‐type (space group: R 3 c , No. 161) and a perovskite‐type structure, is a metastable phase, which can partially decomposed into SnO 2 and Zn 2 SnO 4 above 750°C in atmosphere ambient . Son et al reported that ZnSnO 3 thin film could heteroepitaxially grow on SrTiO 3 (111) substrate and show a high ferroelectric polarization.…”
Section: Introductionmentioning
confidence: 94%
“…161) and a perovskite-type structure, is a metastable phase, which can partially decomposed into SnO 2 and Zn 2 SnO 4 above 750°C in atmosphere ambient. 10,11 Son et al 12 reported that ZnSnO 3 thin film could heteroepitaxially grow on SrTiO 3 (111) substrate and show a high ferroelectric polarization. Zn 2 SnO 4 has an inverse spinel structure with a space group of Fdm.…”
Section: Introductionmentioning
confidence: 99%